Therapeutic Impact of Deep Balloon-assisted Small Bowel Enteroscopy on Red Blood Cell Transfusion - Kalra, Amandeep S.; Walker, Andrew J.; Benson, Mark E.; Guda, Nalini M.; Soni, Anurag; Misha, Mehak; Gopal, Deepak V. (Journal of Digestive Endoscopy, 2020)
Objective Evaluate impact of balloon-assisted deep small bowel enteroscopy on red blood cell transfusion requirement in patients with obscure gastrointestinal (GI) bleeding.Methods Retrospective study of patients, who underwent balloon-assisted deep enteroscopy with double-balloon enteroscopy (DBE) at two tertiary care academic centers (University of Wisconsin and Aurora St. Luke’s Medical Center) over a 55-month consecutive period. Sixty-nine patients with reliable blood transfusion records were identified during this time period. DBE was preceded by small bowel capsule endoscopy (CE) within 1 year in 38 cases. Transfusion requirements 6 months prior and postintervention were measured to see if DBE had any impact on the need for blood transfusions.Results Sixty-nine patients (25 females and 44 males) were included. Mean age ± standard deviation (SD) was 63 ± 17 years. Wilcoxon signed rank test statistics were used to find the difference in the rate of blood transfusion. There was a statistically significant decrease in rate of packed red blood cell (pRBC) transfusion post DBE and endoscopic therapy with coagulation (p < 0.001). Argon plasma coagulation was used to ablate all arteriovenous malformations (AVMs) except in one (subepithelial lesion). Those that required > 5 units pRBC transfusions pre-DBE had the most benefit.Conclusions Our study demonstrates that transfusion requirements are significantly reduced in those undergoing therapy with DBE and coagulation for obscure GI bleed.
Keywords: DBE–double-balloon enteroscopy; OGIB–obscure gastrointestinal bleeding; red blood transfusion; therapeutic endoscopy